SERVQUAL DAN CUSTOMER SATISFACTION INDEX (CSI) : MENGUKUR TINGKAT USABILITAS E-LEARNING PADA PEMBELAJARAN DARING MASA ADAPTASI KEBIASAAN BARU (AKB) PANDEMI COVID-19 DI UNIVERSITAS AL-GHIFARI - Taufiq Rahmat; Eny Nuryani Resmiati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
E-learning is important to be adopted by universities so that they can still have anadvantage during increasingly high competition. Plus the condition of our nation iscurrently entering a new habit adaptation period due to the Covid-19 pandemic.Thus, the implementation of learning is carried out online. To maintain usersatisfaction with the service, it is necessary to evaluate the user usability of theimplementation of e-learning to generate recommendations that can be used as ameans to improve the quality of the system and media used in the future. This studyuses a descriptive method with a quantitative approach that refers to service qualityincluding TERRA which consists of tangible, empathy, reliability, responsiveness,and assurance. The questionnaire instrument uses closed questions, consisting of an assessment between expectations and reality. The scale used in the questionnaireusing a Likert scale was distributed to 100 respondents who were selected based ona simple random sampling technique. The data were analyzed using descriptiveanalysis by calculating the average variable score, then measuring the CustomerSatisfaction Index (CSI). The results showed that overall users were satisfied withthe performance of ServQual's attributes in implementing e-learning at Al-GhifariUniversity during the adaptation period for the new habits of the COVID-19pandemic.